Answer
Here are the solutions for each equation:
1. \( x = -7\log_{\frac{9}{2}}{(2)} \)
2. \( x = 4 \)
3. \( x_{1} = -3, \quad x_{2} = 0 \)
4. \( x_{1} = -1, \quad x_{2} = 3 \)
5. \( x = -0.5 \)
6. \( x = 1 \)
7. \( x_{1} = -2, \quad x_{2} = 2 \)
8. \( x = -3 \)
9. \( x = -2.5 \)
10. \( x_{1} = -1.5, \quad x_{2} = 1 \)
Solution
Solve the equation by following steps:
- step0: Solve for \(x\):
\(12^{x}\times 12^{x}=144\)
- step1: Multiply the terms:
\(12^{2x}=144\)
- step2: Rewrite in exponential form:
\(12^{2x}=12^{2}\)
- step3: Set the exponents equal:
\(2x=2\)
- step4: Divide both sides:
\(\frac{2x}{2}=\frac{2}{2}\)
- step5: Divide the numbers:
\(x=1\)
Solve the equation \( 3^{x+1}=9^{x} \cdot \frac{1}{27} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(3^{x+1}=9^{x}\times \frac{1}{27}\)
- step1: Multiply the terms:
\(3^{x+1}=3^{2x-3}\)
- step2: Set the exponents equal:
\(x+1=2x-3\)
- step3: Move the expression to the left side:
\(x-2x=-3-1\)
- step4: Add and subtract:
\(-x=-3-1\)
- step5: Add and subtract:
\(-x=-4\)
- step6: Change the signs:
\(x=4\)
Solve the equation \( 2^{2 x} \cdot 4^{x+1}=1 \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(2^{2x}\times 4^{x+1}=1\)
- step1: Multiply the terms:
\(2^{4x+2}=1\)
- step2: Rewrite in exponential form:
\(2^{4x+2}=2^{0}\)
- step3: Set the exponents equal:
\(4x+2=0\)
- step4: Move the constant to the right side:
\(4x=0-2\)
- step5: Remove 0:
\(4x=-2\)
- step6: Divide both sides:
\(\frac{4x}{4}=\frac{-2}{4}\)
- step7: Divide the numbers:
\(x=-\frac{1}{2}\)
Solve the equation \( 81 \cdot 9^{x-1}=\frac{1}{27} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(81\times 9^{x-1}=\frac{1}{27}\)
- step1: Multiply the terms:
\(9^{x+1}=\frac{1}{27}\)
- step2: Rewrite in exponential form:
\(3^{2\left(x+1\right)}=3^{-3}\)
- step3: Set the exponents equal:
\(2\left(x+1\right)=-3\)
- step4: Divide both sides:
\(\frac{2\left(x+1\right)}{2}=\frac{-3}{2}\)
- step5: Divide the numbers:
\(x+1=-\frac{3}{2}\)
- step6: Move the constant to the right side:
\(x=-\frac{3}{2}-1\)
- step7: Subtract the numbers:
\(x=-\frac{5}{2}\)
Solve the equation \( \frac{4^{x+1} \times \left(\frac{1}{4}\right)^{-x}}{2^{2 x+1}}=\frac{1}{32} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\frac{4^{x+1}\left(\frac{1}{4}\right)^{-x}}{2^{2x+1}}=\frac{1}{32}\)
- step1: Reduce the fraction:
\(2^{2x+1}=\frac{1}{32}\)
- step2: Rewrite in exponential form:
\(2^{2x+1}=2^{-5}\)
- step3: Set the exponents equal:
\(2x+1=-5\)
- step4: Move the constant to the right side:
\(2x=-5-1\)
- step5: Subtract the numbers:
\(2x=-6\)
- step6: Divide both sides:
\(\frac{2x}{2}=\frac{-6}{2}\)
- step7: Divide the numbers:
\(x=-3\)
Solve the equation \( 3^{x^{2}+2}=9 \cdot \frac{1}{27^{x}} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(3^{x^{2}+2}=9\times \frac{1}{27^{x}}\)
- step1: Simplify:
\(3^{x^{2}+2}=3^{-3x+2}\)
- step2: Set the exponents equal:
\(x^{2}+2=-3x+2\)
- step3: Cancel equal terms:
\(x^{2}=-3x\)
- step4: Move the expression to the left side:
\(x^{2}-\left(-3x\right)=0\)
- step5: Add or subtract both sides:
\(x^{2}+3x=0\)
- step6: Factor the expression:
\(x\left(x+3\right)=0\)
- step7: Separate into possible cases:
\(\begin{align}&x=0\\&x+3=0\end{align}\)
- step8: Solve the equation:
\(\begin{align}&x=0\\&x=-3\end{align}\)
- step9: Rewrite:
\(x_{1}=-3,x_{2}=0\)
Solve the equation \( 5^{x^{2}-1} \cdot \frac{1}{25}=25^{x} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(5^{x^{2}-1}\times \frac{1}{25}=25^{x}\)
- step1: Multiply the terms:
\(5^{x^{2}-3}=25^{x}\)
- step2: Rewrite the expression:
\(5^{x^{2}-3}=5^{2x}\)
- step3: Set the exponents equal:
\(x^{2}-3=2x\)
- step4: Move the expression to the left side:
\(x^{2}-3-2x=0\)
- step5: Factor the expression:
\(\left(x-3\right)\left(x+1\right)=0\)
- step6: Separate into possible cases:
\(\begin{align}&x-3=0\\&x+1=0\end{align}\)
- step7: Solve the equation:
\(\begin{align}&x=3\\&x=-1\end{align}\)
- step8: Rewrite:
\(x_{1}=-1,x_{2}=3\)
Solve the equation \( 2^{x^{2}} \cdot 2^{x^{2}-2}+1=65 \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(2^{\left(x^{2}\right)}\times 2^{x^{2}-2}+1=65\)
- step1: Multiply the terms:
\(2^{2x^{2}-2}+1=65\)
- step2: Move the constant to the right side:
\(2^{2x^{2}-2}=65-1\)
- step3: Subtract the numbers:
\(2^{2x^{2}-2}=64\)
- step4: Rewrite in exponential form:
\(2^{2x^{2}-2}=2^{6}\)
- step5: Set the exponents equal:
\(2x^{2}-2=6\)
- step6: Move the constant to the right side:
\(2x^{2}=6+2\)
- step7: Add the numbers:
\(2x^{2}=8\)
- step8: Divide both sides:
\(\frac{2x^{2}}{2}=\frac{8}{2}\)
- step9: Divide the numbers:
\(x^{2}=4\)
- step10: Simplify the expression:
\(x=\pm \sqrt{4}\)
- step11: Simplify:
\(x=\pm 2\)
- step12: Separate into possible cases:
\(\begin{align}&x=2\\&x=-2\end{align}\)
- step13: Rewrite:
\(x_{1}=-2,x_{2}=2\)
Solve the equation \( 10^{2 x^{2}} \cdot 10^{x+1}=10000 \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(10^{2x^{2}}\times 10^{x+1}=10000\)
- step1: Multiply:
\(10^{2x^{2}+x+1}=10000\)
- step2: Rewrite in exponential form:
\(10^{2x^{2}+x+1}=10^{4}\)
- step3: Set the exponents equal:
\(2x^{2}+x+1=4\)
- step4: Move the expression to the left side:
\(2x^{2}+x+1-4=0\)
- step5: Subtract the numbers:
\(2x^{2}+x-3=0\)
- step6: Factor the expression:
\(\left(x-1\right)\left(2x+3\right)=0\)
- step7: Separate into possible cases:
\(\begin{align}&x-1=0\\&2x+3=0\end{align}\)
- step8: Solve the equation:
\(\begin{align}&x=1\\&x=-\frac{3}{2}\end{align}\)
- step9: Rewrite:
\(x_{1}=-\frac{3}{2},x_{2}=1\)
Solve the equation \( 18^{x} \cdot \frac{1}{4^{x-1}}=\frac{1}{32} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(18^{x}\times \frac{1}{4^{x-1}}=\frac{1}{32}\)
- step1: Simplify:
\(9^{x}\times 2^{-x+2}=\frac{1}{32}\)
- step2: Take the logarithm of both sides:
\(\ln{\left(9^{x}\times 2^{-x+2}\right)}=\ln{\left(\frac{1}{32}\right)}\)
- step3: Evaluate the logarithm:
\(2\ln{\left(3\right)}\times x-\ln{\left(2\right)}\times x+2\ln{\left(2\right)}=\ln{\left(\frac{1}{32}\right)}\)
- step4: Evaluate the logarithm:
\(2\ln{\left(3\right)}\times x-\ln{\left(2\right)}\times x+2\ln{\left(2\right)}=-5\ln{\left(2\right)}\)
- step5: Simplify:
\(\ln{\left(\frac{3^{2}}{2}\right)}\times x+2\ln{\left(2\right)}=-5\ln{\left(2\right)}\)
- step6: Move the constant to the right side:
\(\ln{\left(\frac{3^{2}}{2}\right)}\times x=-5\ln{\left(2\right)}-2\ln{\left(2\right)}\)
- step7: Subtract the numbers:
\(\ln{\left(\frac{3^{2}}{2}\right)}\times x=-7\ln{\left(2\right)}\)
- step8: Divide both sides:
\(\frac{\ln{\left(\frac{3^{2}}{2}\right)}\times x}{\ln{\left(\frac{3^{2}}{2}\right)}}=\frac{-7\ln{\left(2\right)}}{\ln{\left(\frac{3^{2}}{2}\right)}}\)
- step9: Divide the numbers:
\(x=-7\log_{\frac{3^{2}}{2}}{\left(2\right)}\)
- step10: Simplify:
\(x=-7\log_{\frac{9}{2}}{\left(2\right)}\)
Here are the solutions for each equation step by step:
1. **Equation:** \( 18^{x} \cdot \frac{1}{4^{x-1}}=\frac{1}{32} \)
**Solution:**
\[
x = -7\log_{\frac{9}{2}}{(2)}
\]
2. **Equation:** \( 3^{x+1}=9^{x} \cdot \frac{1}{27} \)
**Solution:**
\[
x = 4
\]
3. **Equation:** \( 3^{x^{2}+2}=9 \cdot \frac{1}{27^{x}} \)
**Solution:**
\[
x_{1} = -3, \quad x_{2} = 0
\]
4. **Equation:** \( 5^{x^{2}-1} \cdot \frac{1}{25}=25^{x} \)
**Solution:**
\[
x_{1} = -1, \quad x_{2} = 3
\]
5. **Equation:** \( 2^{2 x} \cdot 4^{x+1}=1 \)
**Solution:**
\[
x = -\frac{1}{2} \quad \text{(or } x = -0.5\text{)}
\]
6. **Equation:** \( 12^{x} \cdot 12^{x}=144 \)
**Solution:**
\[
x = 1
\]
7. **Equation:** \( 2^{x^{2}} \cdot 2^{x^{2}-2}+1=65 \)
**Solution:**
\[
x_{1} = -2, \quad x_{2} = 2
\]
8. **Equation:** \( \frac{4^{x+1} \times\left(\frac{1}{4}\right)^{-x}}{2^{2 x+1}}=\frac{1}{32} \)
**Solution:**
\[
x = -3
\]
9. **Equation:** \( 81 \cdot 9^{x-1}=\frac{1}{27} \)
**Solution:**
\[
x = -\frac{5}{2} \quad \text{(or } x = -2.5\text{)}
\]
10. **Equation:** \( 10^{2 x^{2}} \cdot 10^{x+1}=10000 \)
**Solution:**
\[
x_{1} = -\frac{3}{2}, \quad x_{2} = 1 \quad \text{(or } x_{1} = -1.5, \quad x_{2} = 1\text{)}
\]
These solutions provide the values of \( x \) for each equation.
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution